The STEM Pipeline: The Role of Summer Research Experience in Minority Students’ Graduate Aspirations - Pender, Matea; Marcotte, Dave E.; Sto. Domingo, Mariano R.; Maton, Kenneth I. (Education Policy Analysis Archives, 2010)
Practical research experience has been seen as an important tool to enhance learning in STEM fields and shape commitment to science careers. Indeed, this was a prominent recommendation of the Boyer Commission. Further, there is evidence this is especially important for minority students. In this paper, we examine the role of practical research experience during the summer for talented minority undergraduates in STEM fields. We focus on the link between summer research and STEM PhD program matriculation. We examine evidence on this question using detailed data on students participating in the Meyerhoff Scholarship Program over a 14 year period at the University of Maryland Baltimore County. Our results provide evidence of strong positive effects of summer research on participation in STEM PhD programs. Further, we show that the effects of summer research vary with the frequency and timing of these experiences. The evidence that educational strategies such as summer research experiences improve academic outcomes of minorities is vital, given concern about the science pipeline in the U.S. and the continuing growth in the racial/ethnic diversity of the college-age population.